Association of sequence types, antimicrobial resistance and virulence genes in Indian isolates of Klebsiella pneumoniae: A comparative genomics study. (September 2022) - Sundaresan, Abhirami Krishnamoorthy; Vincent, Keerthana; Mohan, Ganesh Babu Malli; Ramakrishnan, Jayapradha
ABSTRACT: Objectives: Klebsiella pneumoniae genomic surveillance in India was performed to understand the spread of antimicrobial resistant genes across the country over 10 years and to delineate environment and clinical K. pneumoniae through comparative genomics approach. Methods: The genomic data of 153 strains were retrieved from PATRIC. To compare the presence of AMR genes, virulence genes, episomes and their evolutionary relationship in 153 K. pneumoniae genomes, ResFinder, Virulence Factor Database, Plasmid Finder and CSI phylogeny tools were used, respectively. Results: Diverse serotypes were found among the 153 K. pneumoniae isolates, of which K51 (28%) and K64 (21.56%) were majorly found. Most of the K51 isolates belong to ST231 (93.02 %). The number of associated virulence genes ( rmpA, magA, entB, ybtS, iutA, allS ) appeared to be higher in ST231-KL51 and ST23-KL1 isolates. More than 97% of clinical strains have yersiniabactin, aerobactin genes. Importantly, 98% and 62% of the ESBL and carbapenemase-producing isolates harboured ybtS, iutA, and rmpA, magA genes, respectively. The IncF conjugative plasmids are predominant in K. pneumoniae . The phylogenetic analysis clearly separates the environmental strains from clinical and characterised by uncommon STs and serotypes. Conclusion: Our study illustrates K. pneumoniae genomic surveillance in India representing the phylogenetic evolution, STs, AMR, virulence, serotype to provide more attention for immediate treatment and preventing the dissemination of K. pneumoniae .